Extracorporeal life support for refractory out-of-hospital cardiac arrest: Should we still fight for? A single-centre, 5-year experience. (1st February 2016) - Pozzi, Matteo; Koffel, Catherine; Armoiry, Xavier; Pavlakovic, Isabelle; Neidecker, Jean; Prieur, Cyril; Bonnefoy, Eric; Robin, Jacques; Obadia, Jean-François
Abstract: Background: Cardiopulmonary resuscitation displays low survival rate after out-of-hospital cardiac arrest (OHCA). Extracorporeal life support (ECLS) could be suggested as a rescue therapeutic option in refractory OHCA. The aim of this report is to analyze our experience of ECLS implantation for refractory OHCA. Methods: We performed a retrospective observational analysis of our prospectively collected database. Patients were divided into a shockable rhythm (SH-R) and a non-shockable rhythm (NSH-R) group according to cardiac rhythm at ECLS implantation. The primary endpoint was survival to hospital discharge with good neurological recovery. Results: From January 2010 to December 2014 we used ECLS in 68 patients (SH-R, n = 19, 27.9% vs. NSH-R, n = 49, 72.1%) for refractory OHCA. The clinical profile before ECLS implantation was comparable between the groups. Eight (11.7%) patients were successfully weaned from ECLS (SH-R = 31.5% vs. NSH-R = 4.0%, p = 0.01) after a mean period of support of 2.1 days (SH-R = 4.1 days vs. NSH-R = 1.4 days, p = 0.01). Six (8.8%) patients survived to discharge (SH-R = 31.5% vs. NSH-R = 0%, p = 0.00). In the SH-R group 50% of the survivors were discharged without neurological complications. Conclusions: ECLS for refractory OHCA should be limited in consideration of its poor, especially neurological, outcome. Non-shockable rhythms could be considered as a formal contraindication allowing a concentration of our efforts on the shockable rhythms, where the chances of success are substantial.